2015
DOI: 10.1186/s12888-015-0453-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of positive memory training for the treatment of depression within schizophrenia

Abstract: BackgroundDepression is highly prevalent within individuals diagnosed with schizophrenia, and is associated with an increased risk of suicide. There are no current evidence based treatments for low mood within this group. The specific targeting of co-morbid conditions within complex mental health problems lends itself to the development of short-term structured interventions which are relatively easy to disseminate within health services. A brief cognitive intervention based on a competitive memory theory of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…There continue to be new developments addressing specific issues that present with psychosis and the 'third wave' of cognitive therapies are beginning to provide further alternatives. Further research is underway into clozapine resistant patients (Pyle et al, 2016) and imagery approaches to depression (Steel et al, 2015). The interaction, choices and potential synergies between medications, family and social interventions and CBTp, is however still far from being fully explored and understood.…”
Section: Resultsmentioning
confidence: 99%
“…There continue to be new developments addressing specific issues that present with psychosis and the 'third wave' of cognitive therapies are beginning to provide further alternatives. Further research is underway into clozapine resistant patients (Pyle et al, 2016) and imagery approaches to depression (Steel et al, 2015). The interaction, choices and potential synergies between medications, family and social interventions and CBTp, is however still far from being fully explored and understood.…”
Section: Resultsmentioning
confidence: 99%
“…This is relevant because trauma‐exposed individuals with PTSD symptoms experience emotion dysregulation with a prominence of negative affect (Litz, Orsillo, Kaloupek, & Weathers, ) and negative schemas (Foa & Kozak, ; Janoff‐Bulman, ). To this point, the effects of positive memory recall on positive affect and/or self‐representations are supported by experimental (Rusting & DeHart, ), neurobiological (Speer, Bhanji, & Delgado, ) and intervention research (Neshat‐Doost et al, ; Panagioti, Gooding, & Tarrier, ; Schneider et al, ; Steel et al, ). This enhanced positive affect may improve physical and mental health (Steptoe, Dockray, & Wardle, ) by activating positive interpretations of events and pleasant thoughts (Rusting & DeHart, ; Rusting & Larsen, ), improving self‐esteem (Steel et al, ), increasing positive content in thoughts (Fredrickson, ) and reducing negative rumination (Raes et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Other therapeutic approaches suggest that focusing on positive memories builds distress tolerance (i.e., Dialectical Behavioural Therapy; Linehan, ), elicits values (i.e., Acceptance and Commitment Therapy [ACT]; Hayes, Luoma, Bond, Masuda, & Lillis, ), fosters positive self‐/other‐ representations and strengthens the affective therapeutic relationship (i.e., psychoanalysis; Freud, ), increases the self‐actualising tendency (i.e., client‐centred therapy; Rogers, ), and promotes social bonding and supportive relationships (i.e., Seeking Safety; Najavits, Weiss, & Liese, ). Positive memory interventions have been used for individuals with PTSD, such as Broad‐Minded Affective Coping (BMAC; capitalises on positive affect to reciprocally improve cognitions; Tarrier, ), Positive Memory Enhancement Training (targeting retrieval of specific positive memories; Arditte Hall, De Raedt, Timpano, & Joormann, ), and Positive Memory Training (targeting retrieval of specific positive memories; Steel et al, ); however, these protocols were not developed to uniquely and focally address PTSD symptoms and have not been implemented within existing PTSD interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis in this paper was based on data from the PoMeT trial (20), which investigated the impact of Positive Memory Training on depression symptoms of schizophrenia patients (n = 100) in the UK between 2014-2016. The trial received ethical approval from the Berkshire Research Ethics Committee (REC ref 13/SC/0634).…”
Section: Data Sourcementioning
confidence: 99%
“…Patients were assessed at four time points through the 9-month study period: baseline, 3 months, 6 months and 9 months. More details about the PoMeT trial can be found in Steel et al (20).…”
Section: Data Sourcementioning
confidence: 99%